Demographic and Professional Determinants of Emotional Intelligence among Women Journalists in Kerala and Their Impact on Life Satisfaction and Job Satisfaction - R K, Greeshma; D, Dr. Kinslin. (International Journal of Accounting and Economics Studies, 2025)
Emotional Intelligence (EI) is the ability to perceive, regulate, and utilize emotions efficiently. has arisen as a critical psychological asset influencing well-being, adaptability, and occupational success across various professions. In high-pressure fields such as journalism, where emotional labor, tight deadlines, and unpredictable work schedules are routine, EI plays a dynamic role in mediating both personal and professional outcomes. This study investigates the impact of EI on work-life balance, job satisfaction, and life satisfaction among women journalists in Kerala, a state known for its vibrant media landscape and increasing female workforce participation. A sample of 196 women journalists representing diverse media types (print, television, radio, and online) and spanning various age groups and experience levels participated in the study. Employing a mixed-method analytical framework comprising One-Way ANOVA, Pearson correlation, and multiple regression, the research revealed statistically significant variations in overall and dimension-wise EI across age, experience, and media type. Notably, professionals aged 40–49 and those in online media roles demonstrated the highest EI scores, particularly in empathy and motivation. EI showed a strong positive correlation with life satisfaction (r = 0.446), and moderate correlations with job satisfaction (r = 0.323) and work-life balance (r = 0.181). Regression analysis further confirmed that EI significantly predicts these well-being outcomes. These findings underscore the necessity of integrating EI-enhancing interventions within media organizations to foster resilience and satisfaction among women journalists. Beyond psychological implications, the study highlights the economic relevance of Emotional Intelligence (EI) in journalistic organizations. Higher EI scores among mid-career and online media professionals are not only linked to greater well-being but also suggest potential gains in organizational productivity and employee retention. By identifying EI as a predictive variable for satisfaction outcomes, media firms can assess the cost-effectiveness of EI development programs, thereby aligning human capital investments with improved organizational performance.
Keywords: Emotional Intelligence, Women Journalists, Work-Life Balance, Job Satisfaction, Life Satisfaction, Cost-effectiveness